Time course and mechanism of brain oxidative stress and damage for redox active and inactive transition metals overload - Ferrarotti, Nidia Fatima (2016)
The objective of this work was to study the in vivo time course of biochemical processes of oxidative damage in the brain of Sprague-Dawley rats that received an acute overload of the redox active metals iron (Fe) and copper (Cu), and the redox inactive cobalt (Co) and nickel (Ni). Oxidative stress indicators (phospholipid and protein oxidation), glutathione (GSH), antioxidant enzymes and NADPH oxidase activities, and the plasma inflammatory cytokine (IL-6) were measured. The results showed that in brain oxidative mechanisms for both sets of metal are different, however in both cases are irreversible. The mechanism for Fe and Cu oxidative damage is mediated by the generation of the free radical hydroxyl (Fenton reaction and homolytic cleavage of hydroperoxides). Two events of antioxidant protection prior to oxidation of phospholipids and proteins by Fe and Cu are considered. The first process is the use of GSH and the second is the increased activity of the Cu, Zn-SOD and catalase enzymes. The oxidative mechanism for metal redox inactive is the consumption of GSH, NADPH oxidase activation and inflammatory response mediated by IL-6. Co increased protein oxidation as a result of the inflammatory process. Ni produced increments of phospholipid oxidation and SOD activity.